Traditional Chinese Medicine assisted treatment combined with psychological care for a very elderly patient with arterial embolism of the lower extremity (1例超高龄下肢动脉栓塞患者的中医辅助治疗及心理护理) - CHEN Haiyan (陈海燕); FANG Lina (方立娜); FANG Xiaomei (方晓梅) (Association of Integrative Nursing, 2022)
This paper summarized the experience of Traditional Chinese Medicine(TCM) assisted treatment combined with psychological care for a very elderly patient with a arterial embolisms of the lower extremities. A standard procedure of disinfection, isolation and pain management was carried out before surgery. Based on the monitoring of postoperative condition, TCM acupoint application, acupoint sticking and pressing therapy and psychological care were carried out to relieve the postoperative pain and constipation. (本文总结1例下肢动脉栓塞合并便秘的超高龄患者的中医辅助治疗和心理护理经验。术前严格消毒隔离和规范化疼痛管理; 术后加强病情观察, 针对便秘实施中医穴位贴敷和穴位按摩, 同时给予心理护理, 以缓解患者术后便秘及下肢疼痛症状。)